Attitudes Towards and Experience of the Use of Triage Tags in Major Incidents: A Mixed Method Study. Issue 4 (23rd May 2016) - Rådestad, Monica; Lennquist Montán, Kristina; Rüter, Anders; Castrén, Maaret; Svensson, Leif; Gryth, Dan; Fossum, Bjöörn
Abstract: Introduction: Disaster triage is the allocation of limited medical resources in order to optimize patient outcome. There are several studies showing the poor use of triage tagging, but there are few studies that have investigated the reasons behind this. The aim of this study was to explore ambulance personnel attitude towards, and experiences of, practicing triage tagging during day-to-day management of trauma patients, as well as in major incidents (MIs). Methods: A mixed method design was used. The first part of the study was in the form of a web-survey of attitudes answered by ambulance personnel. The question explored was: Is it likely that systems that are not used in everyday practice will be used during MIs? Two identical web-based surveys were conducted, before and after implementing a new strategy for triage tagging. This strategy consisted of a time-limited triage routine where ambulance services assigned triage category and applied triage tags in day-to-day trauma incidents in order to improve field triage. The second part comprised three focus group interviews (FGIs) in order to provide a deeper insight into the attitudes towards, and experience of, the use of triage tags. Data were analyzed using qualitative content analysis. Results: The overall finding was the need for daily routine when failure in practice. Analysis of the web-survey revealed three changes: ambulance personnel were more prone to use tags in minor accidents, the sort scoring system was considered to be more valuable, but it also was more time consuming after the intervention. In the analysis of FGIs, four categories emerged that describe the construction of the overall category: perceived usability, daily routine, documentation, and need for organizational strategies. Conclusion: Triage is part of the foundation of ambulance skills, but even so, ambulance personnel seldom use this in routine practice. They fully understand the benefit of accurate triage decisions, and also that the use of a triage algorithm and color coded tags is intended to make it easier and more secure to perform triage. However, despite the knowledge and understanding of these benefits, sparse incidents and infrequent exercises lead to ambulance personnel's uncertainty concerning the use of triage tagging during a MI and will therefore, most likely, avoid using them. M Rådestad, K Lennquist Montán, A Rüter, M Castrén, L Svensson, D Gryth, B Fossum .Attitudes towards and experience of the use of triage tags in major incidents: a mixed method study .Prehosp Disaster Med .2016 ;31 (4 ):376 –385 .